Enhanced Separation Efficiency and Purity of Circulating Tumor Cells Based on the Combined Effects of Double Sheath Fluids and Inertial Focusing - Li, Bo-Wen; Wei, Kun; Liu, Qi-Qi; Sun, Xian-Ge; Su, Ning; Li, Wen-Man; Shang, Mei-Yun; Li, Jin-Mi; Liao, Dan; Li, Jin; Lu, Wei-Ping; Deng, Shao-Li; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Circulating tumor cells (CTCs) play a crucial role in solid tumor metastasis, but obtaining high purity and viability CTCs is a challenging task due to their rarity. Although various works using spiral microchannels to isolate CTCs have been reported, the sorting purity of CTCs has not been significantly improved. Herein, we developed a novel double spiral microchannel for efficient separation and enrichment of intact and high purity CTCs based on the combined effects of two-stage inertial focusing and particle deflection. Particle deflection relies on the second sheath to produce a deflection of the focused sample flow segment at the end of the first stage microchannel, allowing larger particles to remain focused and entered the second stage microchannel while smaller particles to move into the first waste channel. The deflection of the focused sample flow segment was visualized. Testing by a binary mixture of 10.4 and 16.5 μm fluorescent microspheres, it showed 16.5 μm with separation efficiency of 98% and purity of 90% under the second sheath flow rate of 700 μL/min. In biological experiments, the average purity of spiked CTCs was 74% at a high throughput of 1.5 × 10*8 cells/min, and the recovery was more than 91%. Compared to the control group, the cell viability was 99%. Finally, we validated the performance of the double spiral microchannel using clinical cancer blood samples. CTCs with a concentration of 2-28 counts/mL were separated from all 12 patients’ peripheral blood. Thus, our device could be a robust and label-free liquid biopsy platform in inertial microfluidics for successful application in clinical trials.